Pengaruh Aplikasi "Remaja Cerdik Mobile" Terhadap Pengetahuan, Sikap dan Efikasi Diri Remaja Tentang Pencegahan Prediabetes - Dwi Rizky Novianto; Antono Suryoputro; Bagoes Widjanarko (Berita Kedokteran Masyarakat (BKM), 2019)
The influence of the application of "Clever Teen Mobile" on the knowledge, attitudes and self-efficacy of adolescents about the prevention of prediabetesPurpose: The current lifestyle of adolescents is believed to be the most dominant factor in the increasing incidence of prediabetes. This situation is at high risk of developing Diabetes Mellitus if no lifestyle changes are made. Raising health promotion by utilizing technological sophistication in the form of an android-based application can be a media for health promotion for teenagers. This study aims to determine the effect of android-based applications "Remaja Cerdik Mobile" on adolescent knowledge, attitudes and self-efficacy about prevention of Prediabetes. Method: This study uses a quasi-experimental method with a non equivalent control group design with pretest-posttest design. The number of respondents is 100 high school students in the city of Semarang. Data analysis used the One Way repeated measures ANOVA test.Results: The results of the development of application media obtained material about the knowledge and prevention of prediabetes which includes articles, images, quizzes, videos and tracker updates. Quantitative research shows that there is the influence of android-based applications "Remaja Cerdik Mobile" in increasing adolescents' knowledge, attitude and self-efficacy about prevention of prediabetes. Conclusion: This android-based applications "Remaja Cerdik Mobile" can be an alternative in the use of health promotion media as a means of educational information communication for adolescents in prediabetes prevention.